ORTHOPAEDIC MANAGEMENT OF EARTHQUAKE VICTIMS IN A TERTIARY CARE TEACHING HOSPITAL - CMH RAWALPINDI: Orthopaedic Management of Earthquake Victims - Hafeez, Sohail; Majid, Nasim Ul; Sheikh, Irfan Ali; Hafeez, Ahsan (Pakistan Armed Forces Medical Journal, 2006)
Background: This study is based on the orthopaedic management of casualties coming from earthquake area after 8th October 2005.Duration of the Study: 03 Months.Material and Methods: All the patients requiring orthopaedic managements were subjected to major and minor operations including internal fixation, external fixation and conservative approach.Results: A total 811 major orthopaedic operations were performed by all three orthopaedic teams at CMH Rawalpindi. 192 patients underwent soft procedures and 35 fasciotomies were carried out. 466 fixations were carried out including internal and external and rests were other procedures.Conclusion: It is concluded that proper triage, initial management of wounds and selection of implant play a major role for better outcome in case of disaster casualties.